2011
DOI: 10.1007/s11605-011-1538-2
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Platelet Count in the Outcomes of Hepatectomized Patients with Hepatocellular Carcinoma Exceeding the Milan Criteria

Abstract: Hepatectomy for patients with advanced HCC exceeding MC improves survival, especially for patients with a sufficiently high platelet count, although recurrence rates after initial hepatectomy are high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…However, few studies have focused on the influence of PLT on postoperative recurrence. Although Amano et al [45] showed that decreased PLT was associated with a higher risk of recurrence in HCC, our study indicated that patients with a PLT level ≥ 148 × 10 9 /L had a higher recurrence probability. As prognosis of HCC remains far from satisfactory owing to the high incidence of tumor recurrence, several HCC prognostic models (such as CLIP [48][49][50][51] ) have been proposed.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, few studies have focused on the influence of PLT on postoperative recurrence. Although Amano et al [45] showed that decreased PLT was associated with a higher risk of recurrence in HCC, our study indicated that patients with a PLT level ≥ 148 × 10 9 /L had a higher recurrence probability. As prognosis of HCC remains far from satisfactory owing to the high incidence of tumor recurrence, several HCC prognostic models (such as CLIP [48][49][50][51] ) have been proposed.…”
Section: Discussioncontrasting
confidence: 86%
“…First and most important, although there was an adverse relationship between PLT and plateletbased indices, high levels of all predicted a high HCC recurrence. This dichotomy may due to the fact that although thrombocytopenia/low PLT has been identified as a crucial risk factor for HCC formation [10,11] and prognosis [44][45][46][47] , it was identified as a favorable factor for HCC prognosis in our study and several others [42,43] . In addition, our limited study population included numerous variables that may have contributed to the discrepancy.…”
Section: A B C D E Fmentioning
confidence: 59%
See 1 more Smart Citation
“…Prognosis is limited when it presents at advanced stage, as is frequent. Thrombocytopenia associated with liver fibrosis has been suggested as a cirrhosis surrogate (7), to be potentially useful in screening for patients at risk of HCC (8) and for prognosis (911). In this study, we compared several clinical parameters of patients with small and larger HCCs and report that different parameter patterns could be discerned.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, evaluating molecular markers requires extra time and effort, as well as increased cost. Therefore, routine laboratory assessments, including γ-glutamyl transpeptidase (GGT) (7), monocyte count (8), platelet count (9) and neutrophil-to-lymphocyte ratio (10) have been developed to be predictive factors for survival in HCC.…”
Section: Introductionmentioning
confidence: 99%